Daratumumab-based regimen for newly diagnosed multiple myeloma patients with paraskeletal plasmacytomas: a retrospective study in a single center - Xu, Shuiqing; Chen, Wenming; Li, Yanchen (Hematology (Luxembourg), 2024)
To analyze the efficacy of daratumumab-based regimen in newly diagnosed multiple myeloma(NDMM) patients with paraskeletal plasmacytomas (PPs). The medical data of 28 NDMM patients with PPs were retrospectively analyzed. The daratumumab-based regimen was divided into group A, and the daratumumab-free regimen was divided into group B. The risk factors, efficacy, and overall survival (OS) were compared between the two groups. The results of univariate COX regression analysis showed that only the grouping and creatinine were statistically significant. The HR value of group A was 0.30(0.10-0.88, = 0.029), which was a protective factor for patient survival, and the HR value of creatinine was 1.00(1.00-1.01, = 0.026), which was a risk factor for patient survival. There was a statistically significant difference in efficacy between the two groups, = 0.025 < 0.05. The results showed that the efficacy of group A was better. There was a statistically significant difference in OS between the two groups (54:27, = 0.002). The results indicated that the treatment regimens containing daratumumab could prolong the OS of patients, suggesting that for MM patients with extramedullary disease(EMD), daratumumab-based combination treatment regimens can be given priority.